The Curricular Dichotomy in Islamic Education: Concepts and Cross-Institutional Implementation at SMAN 1 Banjaran and MA Al-Falah Soreang - Radini Teza Inten; Muhamad Iqbal Fathurrahman (AIM: Journal of Islamic Education Management, 2025)
The moral degradation of Indonesian adolescents presents a serious challenge requiring special attention from the education sector. This study aims to compare the concepts and implementation of Islamic Religious Education (PAI) in formal public schools (SMAN 1 Banjaran) and formal schools based on Islamic boarding schools (MA Al-Falah Soreang). This research employed a qualitative approach with a comparative study design. Data were collected through in-depth interviews with 10 informants (principals, curriculum vice-principals, PAI teachers, and student activity coordinators), participant observation, and documentation. Data analysis was conducted using the Miles & Huberman interactive model. The findings reveal that both institutions implement the seven dimensions of Islamic education according to Abdullah Nashih Ulwan (faith education, moral education, physical education, rational education, personality education, social education, and sexual education), yet with significantly different levels of intensity, methods, and duration of habituation. SMAN 1 Banjaran integrates PAI with the national curriculum, whereas MA Al-Falah internalizes Islamic boarding school values into a 24-hour culture. This study concludes that the success of PAI implementation is largely determined by the integration of formal learning, sustainable religious culture habituation, and educator role modeling. These findings recommend the adoption of routine habituation programs from Islamic boarding schools into public schools and increased technological adaptation from public schools into Islamic boarding schools